2008
DOI: 10.1001/archneur.65.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuropathological Features of the Arctic APP Gene Mutation Causing Early-Onset Alzheimer Disease

Abstract: Background: A majority of mutations within the ␤amyloid region of the amyloid precursor protein (APP) gene cause inherited forms of intracerebral hemorrhage. Most of these mutations may also cause cognitive impairment, but the Arctic APP mutation is the only known intra-␤-amyloid mutation to date causing the more typical clinical picture of Alzheimer disease.Objective: To describe features of 1 Swedish and 1 American family with the previously reported Arctic APP mutation.Design, Setting, and Participants: Aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 24 publications
5
82
0
Order By: Relevance
“…Interestingly, hemorrhages are uncommon, whereas parenchymal plaques are abundant in patients with the Flemish-and Arctic-type mutations (Brooks et al, 2004;Basun et al, 2008). This supports the role of Aβ42 in amyloid accumulation localization, as suggested in animal studies.…”
Section: Aβ Isoforms In Hchwa-d Vasculaturesupporting
confidence: 76%
“…Interestingly, hemorrhages are uncommon, whereas parenchymal plaques are abundant in patients with the Flemish-and Arctic-type mutations (Brooks et al, 2004;Basun et al, 2008). This supports the role of Aβ42 in amyloid accumulation localization, as suggested in animal studies.…”
Section: Aβ Isoforms In Hchwa-d Vasculaturesupporting
confidence: 76%
“…Synaptic loss might be closely linked to the learning and memory deficits in AD (Palop et al, 2006;Small, 2008). AD, an age-related neurodegenerative disorder with cognitive decline, is believed to be initiated by neural accumulation of amyloid-β (Aβ) (Basun et al, 2008). Many studies have found synaptic loss observed in human AD brains (Scheff et al, 2011), AD animal brains (Oddo et al, 2003) and hippocampal slices exposed to Aβ in vitro cultures, with reduced synapse and spine numbers (Shankar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several epidemiological studies have also revealed their association with some complex human diseases, such as cancers, 32 cardiovascular disorders 33 and neurodegenerative diseases (Parkinson disease, Alzheimer disease etc.). [34][35][36][37][38] Moreover, disease-associated SNPs in miRNA or miRNA target sites make disease pathway more complex and are often involved in susceptibility or the onset of diseases. 39 In a landmark study, Abelson et al discovered a single-base mutation (var321) in a highly conserved sequence of 3'UTR of Slitrk1 in Tourette syndrome patients.…”
Section: Resultsmentioning
confidence: 99%